The unseen pain: Lived experiences of intimate partner violence victims in South Africa - Daniel Lesiba Letsoalo; Selogile Philda Seeletse; Mahlatsi Venolia Semenya (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
Intimate partner violence (IPV) constitutes a significant global public health problem. Studies of this phenomenon in South Africa are concentrated in urban and semi-urban areas, leaving rural areas unexplored. To bridge this knowledge gap, a qualitative study grounded in social constructivism and a single case study design was conducted to explore the lived experiences of victims of IPV receiving counseling services at the Bapong Crisis Centre, situated in a rural part of North West Province, South Africa. Data were generated from semi-structured interviews with 19 purposively selected IPV victims and deductively analyzed using reflective thematic analysis (RTA) through the lenses of Bonanno’s four-component model. The study found that most participants had negative experiences. The study also found that victims suffered negative emotional, psychological, physical, and social effects and used various coping mechanisms. These insights underscore the need for focused interventions, including mental health services, domestic violence prevention initiatives, and culturally sensitive programs designed to tackle power imbalances and emotional trauma within abusive intimate relationships.